PROSES CRUSHING MATERIAL LIMESTONE UNTUK BAHAN BAKU DALAM PROSES PRODUKSI SEMEN DI PT SEMEN BATURAJA (PERSERO) TBK - Alnando Yuandi; Safaruddin (JIMR : Journal Of International Multidisciplinary Research, 2022)
Cement is the main raw material in infrastructure development. Good infrastructure is supported by a good cement production process, so competent engineers are needed in the cement production process. This activity aims to understand the workings of the limestone crusher used in the cement manufacturing process at PT Semen Baturaja (Persero) Tbk. The data collection methodology in this activity, namely taking references from journals and books about the cement production process (secondary data), as well as interviews and direct observation with field supervisors and equipment operators in the cement production process (primary data). The data that has been obtained is then showed so that it is known that in the process of crushing the limestone material at PT Semen Baturaja (Persero) Tbk, the crusher used is a hammer crusher type hydraulic unit with 2 hammers flanking each other to crush the material. Limestone is the most important raw material in the process of making cement.